Characteristics of clinically node negative breast cancer patients needing preoperative MRI - Madekivi Vilma; Boström Pia; Vahlberg Tero; Aaltonen Riitta; Salminen Eeva (Elsevier Ltd, 2022)
BACKROUND: International guidelines do not recommend magnetic resonance imaging (MRI) for all breast cancer patients at primary diagnostics. This study aimed to understand which patient or tumor characteristics are associated with the use of MRI. The role of MRI among other preoperative imaging methods in clinically node negative breast cancer was studied.
MATERIAL AND METHODS: Patient and tumor characteristics were analyzed in association with the use of MRI by multivariable logistic regression analysis in 461 patients. Primary tumor size was compared between MRI, mammography (MGR), ultrasound (US) and histopathology by Spearman correlation. The delays in surgery and diagnosis were analyzed among patients with or without MRI, and axillary reoperations were evaluated.
RESULTS: Age (p < 0.0001), primary operation method (p < 0.0001), tumor histology (p < 0.0001) and HER2 status (p = 0.0064) were associated with the use of MRI. Spearman correlations between tumor size in histopathology and the difference in tumor size between histopathology and imaging methods were 0.52 in MGR, 0.66 in US and 0.36 in MRI (p < 0.0001 for all). A seven-day delay in surgical treatment was observed among patients with MRI compared to patients without MRI (p < 0.0001). Axillary reoperation rates were similar in patients with or without MRI (p = 0.57).
CONCLUSION: Patient selection through prearranged characterization is important in deciding on optimal candidates for preoperative MRI among breast cancer patients. MRI causes moderate delays in primary breast cancer surgery. Preoperative MRI is useful in the evaluation of tumor size but might be insufficient in detecting lymph node metastases